2000
DOI: 10.1002/1097-0142(20000715)89:2<255::aid-cncr8>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Early and late recurrence after gastrectomy for gastric carcinoma

Abstract: BACKGROUND To the authors' knowledge, there are few studies regarding the predictors of early and late recurrence after gastrectomy for gastric carcinoma, and it is unknown whether prognostic factors can be applied to the timing of recurrence. The current study analyzed patients who died of recurrent gastric carcinoma and clarified histopathologic indicators associated with early and late recurrence. METHODS The study included 138 patients who died of recurrent gastric carcinoma after gastrectomy that was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
112
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 14 publications
10
112
3
2
Order By: Relevance
“…Either as described in the previous studies or in our multivariate survival analysis, the depth of invasion, lymph node or distant metastasis, and TNM staging are independent prognostic indicators in gastric cancers (25,26). The heparanase mRNA expression had a statistical correlation with those indicators.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Either as described in the previous studies or in our multivariate survival analysis, the depth of invasion, lymph node or distant metastasis, and TNM staging are independent prognostic indicators in gastric cancers (25,26). The heparanase mRNA expression had a statistical correlation with those indicators.…”
Section: Discussionsupporting
confidence: 67%
“…Increased lymphatic and venous invasion is possible evidence of tumor angiogenesis. Many reports have shown that the presence of lymphatic and/or venous invasion is a strong risk factor for nodal metastasis, distant metastasis, and tumor recurrence in gastric cancer (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was demonstrated that both the macroscopic appearance and depth of invasion are independent prognostic indicators in gastric carcinoma. 13 Thus, the expression of heparanase in gastric carcinoma may correlate with a more aggressive course.…”
Section: Discussionmentioning
confidence: 99%
“…A Volume of 7 ml of total RNA isolated from approximately 10 000 cells were mixed with 1 ml of oligo-(dT) [12][13][14][15][16][17][18] primer, 1 ml of random hexamers primer (N 6 ), and 1 ml of 10 mM dNTPs in a total volume of 10 ml. They were heat denaturated at 651C for 5 min, and then chilled in ice.…”
Section: Rt-pcr Of Microdissected Cellsmentioning
confidence: 99%
“…Statistically significant differences in risk factors for metastases at different time intervals after definitive treatment have been demonstrated in other cancers, such as gastric and hepatocellular carcinomas. 8,9 Shiraishi et al 8 have demonstrated that, compared with patients who had a late recurrence, patients who had an early recurrence of gastric carcinoma had a significantly increased likelihood of having a larger tumor size at presentation, lymphatic invasion, extensive lymph node metastasis, and more advanced initial stage of disease. In examining hepatocellular carcinoma, multivariate analysis by Poon et al 9 observed that preoperative ''tumor rupture'' and vascular invasion were significant risk factors for early intrahepatic recurrence, whereas cirrhosis was a significant risk factor for late intrahepatic recurrence.…”
mentioning
confidence: 99%